1984
DOI: 10.2170/jjphysiol.34.1
|View full text |Cite
|
Sign up to set email alerts
|

Force-velocity relation and contractility in striated muscles.

Abstract: This review deals with the contractility of striated muscles as made evident in the force and the shortening velocities in various contractions. The contractility, that is, the capability of contraction, can be expressed using two parameters. One is the maximum tension during isometric contraction and the other, the maximum shortening velocity during isotonic contraction under zero load.Shortening velocity is a function of load, which is equal to the muscle tension during isotonic contraction, and the maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 51 publications
0
11
0
1
Order By: Relevance
“…and (5)) are expressed as functions of dimensionless length (' M and' T ), velocity (ṽ M ), and force (normalized by f M o ) so they can be scaled to model a variety of human and animal muscles [23,37]. We have developed default force curves for the musculotendon model that have been fit to experimental data [41][42][43][44][45][46]. These curves can be adjusted to model muscle and tendon whose characteristics deviate from these default patterns.…”
Section: Musculotendon Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…and (5)) are expressed as functions of dimensionless length (' M and' T ), velocity (ṽ M ), and force (normalized by f M o ) so they can be scaled to model a variety of human and animal muscles [23,37]. We have developed default force curves for the musculotendon model that have been fit to experimental data [41][42][43][44][45][46]. These curves can be adjusted to model muscle and tendon whose characteristics deviate from these default patterns.…”
Section: Musculotendon Modelsmentioning
confidence: 99%
“…[41,42]. Data points in panels (c) and (d) denote experimental data for the force-length [43,44] and force-velocity [45,46] curves. The default curves used in the musculotendon models are shown in comparison to these experimental data.…”
Section: Musculotendon Modelsmentioning
confidence: 99%
“…The order of the ramp protocol was randomized. All experiments were conducted at a constant temperature of 12 • C ± 0.1 • C. At this temperature, the fibers proved very stable and able to withstand active ramp protocols over an extended period of time as well as prolonged activations (Ranatunga, 1982(Ranatunga, , 1984Bottinelli et al, 1996;Tomalka et al, 2017).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…From these the maximum velocity of unloaded muscle fibre or contractile element, V, , , is one of the most widely studied parameters (Mason et al 1970, Parmley et al 1972, Grossman et al 1972, Urschel et al 1980). Correspondence Even if its specificity as an index of contractility is questioned both on a theoretical and experimental basis (Pollack 1970, Brady 1979, Mashima 1984, only few, if any, other indices of contractility based on the fundamental principles of muscle contraction are currently available for intact heart examinations. O n the other hand, in a recent study V, , , has been suggested to be a valid parameter of contractility on the level of sarcomere (Daniels et al 1984).…”
mentioning
confidence: 99%